Above the Law. Police and the excessive use of force. Brutalitas polisi. Penggunaan kekerasan yang berlebihan - SKOLNICK, Jerome H. (CIPTA MANUNGGAL, 2001)
Above the law. Police and the excessive use of force. Brutalitas polisi. Penggunaan ..